A Crosstalk Between Brachypodium Root Exudates, Organic Acids, and Bacillus velezensis B26, a Growth Promoting Bacterium - Sharma, Meha; Saleh, Dina; Charron, Jean-Benoit; Jabaji, Suha (Frontiers in Microbiology, 2020)
Plant growth-promoting rhizobacteria (PGPR) are associated with plant roots and use organic compounds that are secreted from root exudates as food and energy source. Root exudates can chemoattract and help bacteria to colonize the surface of plant roots by inducing chemotactic responses of rhizospheric bacteria. In this study, we show that root colonization of Brachypodium distachyon by Bacillus velezensis strain B26 depends on several factors. These include root exudates, organic acids, and their biosynthetic genes, chemotaxis, biofilm formation and the induction of biofilm encoding genes. Analysis of root exudates by GC-MS identified five intermediates of the TCA cycle; malic, fumaric, citric, succinic, oxaloacetic acids, and were subsequently evaluated. The strongest chemotactic responses were induced by malic, succinic, citric, and fumaric acids. In comparison, the biofilm formation was induced by all organic acids with maximal induction by citric acid. Relative to the control, the individual organic acids, succinic and citric acids activated the epsD gene related to EPS biofilm, and also the genes encoding membrane protein (yqXM) and hydrophobin component (bslA) of the biofilm of strain B26. Whereas epsA and epsB genes were highly induced genes by succinic acid. Similarly, concentrated exudates released from inoculated roots after 48 h post-inoculation also induced all biofilm-associated genes. The addition of strain B26 to wild type and to icdh mutant line led to a slight induction but not biologically significant relative to their respective controls. Thus, B26 has no effect on the expression of the ICDH gene, both in the wild type and the mutant backgrounds. Our results indicate that root exudates and individual organic acids play an important role in selective recruitment and colonization of PGPR and inducing biofilm. The current study increases the understanding of molecular mechanisms behind biofilm induction by organic acids.